DIGITAL CULTURAL DIPLOMACY: STRATEGIC COMMUNICATION AND SOFT POWER IN A NETWORKED WORLD - Abdul Rahman (Social Studies and Humanities Journal (SOSHUM), 2025)
The digital globalization era has fundamentally transformed cultural diplomacy from conventional state-centric approaches toward network-based digital cultural diplomacy. This transformation redefines how soft power is constructed and distributed within an ecosystem dominated by global platforms and algorithms. This study employs a systematic narrative review of global literature from 2016-2026 indexed in Scopus, Web of Science, and Google Scholar to synthesize the paradigm shifts in international communication. The findings reveal a decentralization of narrative authority, where non-state actors, such as diasporas and digital influencers, serve as crucial quasi-diplomatic agents. Diplomatic effectiveness has shifted from one-way dissemination to interactive dialogue and narrative co-creation, prioritizing authenticity and storytelling. However, significant challenges persist, including the digital divide, algorithmic gatekeeping, and a trust crisis driven by disinformation. Successful digital cultural diplomacy requires a strategic integration of technological capacity, authentic audience engagement, and multi-actor collaboration to maintain national narrative resilience in a networked world.